Faktor-faktor Yang Mempengaruhi Kualitas Pelaporan Keuangan Pada Hotel Berbintang Di Surakarta - Rayi Diah Pratiwi; Sri Laksmi Pardanawati; Yuwita Ariessa Pravasanti (Nur Science Institute, 2023)
This study aims to analyze the factors that influence the quality of financial reporting at five-star hotels in Solo. This research uses quantitative research methods. The population of this research is Star Hotels in Solo. The sampling of this research used purposive sampling method. The data collection used is primary data in the form of a questionnaire. The data analysis method used in this study is multiple linear regression analysis with a significance level of 5% or 0.05. The results show that the quality of financial reporting is influenced by the internal control system, the use of information technology and the conformity of accounting standards. The linear regression equation is obtained as follows: financial reporting quality (Y) = -9.346 + 0.615X1 + 0.366X2 + 0.374X3 + e. This is indicated by the significance value of the internal control system variable 0.000 <0.05, the use of information technology 0.004 <0.05, and the conformity of accounting standards 0.006 <0.05. The significance value in the simultaneous test is 0.000.